Financial Statement Analysis - Davidson, Wallace (Wiley, 2020)
This book presents financial statements as a set of dynamic instruments that can be used for accurate, relevant, and timely financial decisions. It focuses on the economic and financial conditions that cause statements to change and discover how businesses can manage liquidity, debt, and profitability. Plus, explore effect ratios, causal ratios, pro forma analysis, sustainable growth, and much more. Key topics covered include: valuation techniques, effect ratios, DuPont system for analyzing profitability, causal analysis. how to conduct a financial statement analysis, users of financial statements, forecasting sustainable growth, and bankruptcy prediction models.
Online resource; Title from title page (viewed July 21, 2020)
Keywords: Financial statements; Managerial accounting; Comptabilité de gestion